Determination of brain water content by dry/wet weight measurement for the detection of experimental brain edema - Kozler, P; Marešová, D; Pokorný, J (Physiological research, 2022)
Brain edema is a fatal pathological state in which brain volume increases as a result of abnormal accumulation of fluid within the brain parenchyma. A key attribute of experimentally induced brain edema - increased brain water content (BWC) - needs to be verified. Various methods are used for this purpose: specific gravimetric technique, electron microscopic examination, magnetic resonance imaging (MRI) and dry/wet weight measurement. In this study, the cohort of 40 rats was divided into one control group (CG) and four experimental groups with 8 rats in each group. The procedure for determining BWC using dry/wet weight measurement was initiated 24 h after the completion of edema induction by the water intoxication method (WI group); after the intraperitoneal administration of Methylprednisolone (MP) together with distilled water during edema induction (WI+MP group); 30 min after osmotic blood brain barrier disruption (BBBd group); after injection of MP via the internal carotid artery immediately after BBBd (BBBd + MP group). While induction of brain edema (WI, BBBd) resulted in significantly higher BWC, there was no increase in BWC in the MP groups (WI+MP, BBBd+MP), suggesting a neuroprotective effect of MP in the development of brain edema.
Keywords: hematoencefalická bariéra; edém mozku; Blood-Brain Barrier; Rats; Methylprednisolone; mozek; Water; Animals; Edema; krysa rodu Rattus; methylprednisolon; Brain Edema; edém; zvířata; Brain; voda